1988
DOI: 10.1111/j.1439-0507.1988.tb03869.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics Correlated with Different Fungi Causing Vulvovaginal Mycosis/Klinische Charakteristika der Vulvovaginalmykose in Abhängigkeit von der Erregerart

Abstract: Summary: Vulvovaginal mycosis is primarily caused by 2 species of fungi, Candida albicans and Torulopsis glabrata. Certain clinical characteristics of vulvovaginal mycosis caused by different fungi were studied. Of the 314 cases of vulvovaginal mycosis, 259 were caused by C. albicans, 24 by Candida species other than C. albicans, 27 by T. glabrata, one by Rhodotorula, and 3 by C. albicans and T. glabrata together. The age distribution showed significantly more patients (p <0.01) under the age of 30 in the C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Infections are more likely in the third trimester than other periods [85]. Although, in general, C. albicans is also the most common species among pregnant women, some studies have found NAC species, such as C. tropicalis , predominating [8,31,87,88]. Low socioeconomic background, poor education, non-white race, and underling medical conditions are commoner in NAC vaginitis [5,46].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Infections are more likely in the third trimester than other periods [85]. Although, in general, C. albicans is also the most common species among pregnant women, some studies have found NAC species, such as C. tropicalis , predominating [8,31,87,88]. Low socioeconomic background, poor education, non-white race, and underling medical conditions are commoner in NAC vaginitis [5,46].…”
Section: Risk Factorsmentioning
confidence: 99%